2020
DOI: 10.1038/s41540-020-00144-8
|View full text |Cite|
|
Sign up to set email alerts
|

Signatures of co-deregulated genes and their transcriptional regulators in colorectal cancer

Abstract: The deregulated genes in colorectal cancer (CRC) vary significantly across different studies. Thus, a systems biology approach is needed to identify the co-deregulated genes (co-DEGs), explore their molecular networks, and spot the major hub proteins within these networks. We reanalyzed 19 GEO gene expression profiles to identify and annotate CRC versus normal signatures, single-gene perturbation, and single-drug perturbation signatures. We identified the co-DEGs across different studies, their upstream regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 139 publications
(166 reference statements)
1
14
0
Order By: Relevance
“…In this study, we provide the first evidence demonstrating that CTSE overexpression is significantly correlated with inferior clinical outcomes and acts as an unfavorable predictive biomarker for rectal cancer patients treated with preoperative CCRT. In addition, it has been reported that CTSE is upregulated in CRC tissue samples compared with normal controls [17], further supporting our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we provide the first evidence demonstrating that CTSE overexpression is significantly correlated with inferior clinical outcomes and acts as an unfavorable predictive biomarker for rectal cancer patients treated with preoperative CCRT. In addition, it has been reported that CTSE is upregulated in CRC tissue samples compared with normal controls [17], further supporting our findings.…”
Section: Discussionsupporting
confidence: 92%
“…LINCS datasets, along with others, have been used to identify repurposing candidates from drugs that can reverse the expression profiles of cancer-specific gene signatures (obtained by comparing expression of cancer cells with normal cells; refs. [83][84][85]. DNNs trained on drug-perturbed transcriptional profiles from LINCS have also been used to predict the therapeutic use category for drugs (e.g., vasodilator, antineoplastic) and to prioritize repurposing candidates by their chemical structural similarity with approved cancer drugs (86).…”
Section: Drug Repurposingmentioning
confidence: 99%
“…Furthermore, high CDK1 expression is predominant in patients with resistance to 5-fluorouracil (5-Fu), a common CRC treatment, and it seems to reduce the effect of chemotherapy (Zhu et al, 2020). An upregulation of CDK1 in CRC has been also observed in response to other drugs such as: betaxol, penbutolol and propofol amongst others (Mastrogamvraki and Zaravinos, 2020).…”
Section: Cyclin-dependent Kinase Expression In Human Colorectal Cancermentioning
confidence: 99%
“…CDK2, 4 and 6 levels in CRC are closely related to the Rb protein hyperphosphorylation, which seems to promote cancer progression. CDK4/6 is usually amplified in colon tumors compared to healthy epithelium ( Mastrogamvraki and Zaravinos, 2020 ; Jardim et al, 2021 ). Abundant levels of CDK4 are especially observed in CRC patients with enhanced dysplasia and are correlated to increased tumor cell proliferation ( Zhang et al, 1997 ; Bartkova et al, 2001 ).…”
Section: Cyclin-dependent Kinase Expression In Human Colorectal Cancermentioning
confidence: 99%